Efficacy and safety of switching from bosentan or ambrisentan to macitentan in pulmonary arterial hypertension: A systematic review and meta-analysis - Li, Jie; Yang, Zu-Yuan; Wang, Shang; Yuan, Ping; Zhao, Qin-Hua; Gong, Su-Gang; Qiu, Hong-Ling; Luo, Ci-Jun; Li, Hui-Ting; Zhang, Rui; Wu, Wen-Hui; Liu, Jin-Ming; et al. (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background There is little evidence of the effectiveness of switching from the endothelin receptor antagonists (ERAs) bosentan and ambrisentan to a novel ERA, macitentan, in patients with pulmonary arterial hypertension (PAH). Therefore, a systematic review and meta-analysis was performed to evaluate the efficacy and safety of patients with PAH switching from other ERAs to macitentan. Methods We retrieved the relevant literature published before January 2022 for the meta-analysis from the PubMed, EMBASE, and Cochrane Library databases. Efficacy included changes in the six-minute walk distance (6MWD), World Health Organization functional class (WHO-FC), N-terminal pro-brain natriuretic peptide (NT-proBNP) levels, hemodynamics, echocardiography and survival. Results Nine studies, consisting of 408 PAH patients, that met the inclusion criteria were included. The switch from bosentan or ambrisentan to macitentan effectively increased the 6MWD by 20.71 m (95% CI : 10.35-31.07, P < 0 .00001, I2 = 0%). Six months after conversion, the tricuspid annular plane systolic excursion was found to improve from 19.0 ± 4.0 mm to 21.0 ± 5.0 mm in adults and from 16.00 ± 5.0 mm to 18.25 ± 4.8 mm in children. Ordinal logistic regression showed that the WHO-FC significantly improved by 0.412 (95% CI: 0.187-0.908, P = 0.028). The switch did not show significant improvement in NT-proBNP levels. In addition, the switch was well tolerated. Conclusions The switch from bosentan or ambrisentan to macitentan significantly increased the 6MWD in PAH patients, improved the WHO-FC, and exerted safety benefits. The effects of the switch on NT-proBNP levels, hemodynamics, and echocardiography still need to be further confirmed.